The impact of complications on a programme of enhanced recovery in colorectal surgery - Tebala, Giovanni D. (BMC Surg, 2018)
BACKGROUND: The advantages of Enhanced Recovery (ER) programmes are well known, in terms of improved overall experience of the patients, which associates with low morbidity and reduced length of stay. As a result, the pattern of morbidity is changing and some patients may develop complications after discharge. Aim of this work was to evaluate the impact of morbidity and related outcomes such as unplanned readmission and reoperation rate on an ER programme in colorectal surgery. METHODS: Prospectively collected clinical data of patients who underwent colorectal resection have been retrospectively analysed. Endpoints were: 90-day mortality and morbidity, length of hospital stay (LOS) and rate of unplanned readmissions and reoperations. RESULTS: Mortality and morbidity did not change in the analysed period, but LOS reduced significantly. Main determinant of postoperative LOS was the type of surgical approach, laparoscopy being associated with earlier discharge. LOS was longer in patients who developed complications. Morbidity and reoperation rate were significantly higher in patients discharged after day 4. Majority of complications happened in patients who were still in the hospital. However, the few patients who developed complications after discharge did not have a worse outcome if compared to those who had complications in hospital. CONCLUSIONS: ER protocols must become integral part of the perioperative management of colorectal patients. ER and laparoscopy have a synergic effect to improve the postoperative recovery and reduce morbidity. Early discharge of patients does not affect the outcome of postoperative complications.